2021
DOI: 10.1186/s13019-021-01650-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery under cardiopulmonary bypass in pregnancy: report of four cases

Abstract: Background Open heart surgery during pregnancy is relatively rare at home and abroad, and there is a higher risk and probability of maternal and infant death. How to carry out heart valve replacement under cardiopulmonary bypass (CPB) under the premise of ensuring the safety of mother and child is the focus of attention at home and abroad. Case introduction We reported four cases of cardiac surgeries under CPB during pregnancy performed in our hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Cardiac surgery is also associated with a high risk for the fetus. Clinical guidelines recommend postponing cardiac surgery as much as possible until 6 weeks postpartum, and if not possible then to perform cardiac surgery in the second trimester between 13–28 weeks of pregnancy [ 139 , 140 ]. In some cases, the fetus may have transient or spontaneous bradycardia, which may subside at the end of surgery.…”
Section: From Pathophysiology To Multidisciplinary Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac surgery is also associated with a high risk for the fetus. Clinical guidelines recommend postponing cardiac surgery as much as possible until 6 weeks postpartum, and if not possible then to perform cardiac surgery in the second trimester between 13–28 weeks of pregnancy [ 139 , 140 ]. In some cases, the fetus may have transient or spontaneous bradycardia, which may subside at the end of surgery.…”
Section: From Pathophysiology To Multidisciplinary Assessmentmentioning
confidence: 99%
“…Prematurity and stillbirth occur most frequently in urgent cases, accompanied by high surgical risk, multiple maternal co-morbidities or low gestational age [ 145 ]. Peri-operatively, administration of progesterone prevents uterine contractions and magnesium sulphate and atosiban contribute to fetal protection and maintenance of viability [ 140 ]. It is recommended as much as possible to reduce the CBP time, increase the infusion rate and continue antibiotic therapy for up to 6 weeks after surgery [ 151 ].…”
Section: From Pathophysiology To Multidisciplinary Assessmentmentioning
confidence: 99%
“…[3,4] Olgumuzda da olduğu gibi, KPB'ye başlamadan hemen önce bebeğin sezaryen ile doğumunun gerçekleştirilmesi güvenli seçenek olarak görülmektedir. [5] Minimal invaziv kalp cerrahisi, son yıllarda yaygınlaşarak birçok merkezde uygulanmaya başlanmıştır. Minimal invaziv robotik cerrahi…”
Section: öZunclassified
“…You et al [ 2 ] demonstrated that with the use of cardiopulmonary bypass (CPB), we were able to successfully conduct cardiac surgery on four pregnant women who had heart problems. The other two women carried on with their pregnancies following heart surgery, while two of them underwent simultaneous cardiac surgery and cesarean sections.…”
Section: Reviewmentioning
confidence: 99%